2009
DOI: 10.1002/ps.1789
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for 2,4‐D mineralisation in Mediterranean soils: impact of moisture content and temperature

Abstract: This study shows that, although soil microbiota can adapt to rapid mineralisation of 2,4-D, this microbial activity is strongly dependent on climatic parameters. It suggests that only limited pesticide biodegradation occurs under Mediterranean climate, and that arable Mediterranean soils are therefore fragile and likely to accumulate pesticide residues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
12
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 27 publications
5
12
1
Order By: Relevance
“…The pesticide‐degrading ability of the soil microbiota can be impaired by harsh summer conditions 32. In addition, 2,4‐D mineralisation was shown to be very low in Mediterranean soils incubated at relatively high temperature and low moisture content 33. These studies underline the importance of temperature and moisture content on the pesticide‐degrading ability of the soil microbiota, which accomplishes a key ecosystemic service responsible for natural pesticide attenuation.…”
Section: Discussionmentioning
confidence: 76%
“…The pesticide‐degrading ability of the soil microbiota can be impaired by harsh summer conditions 32. In addition, 2,4‐D mineralisation was shown to be very low in Mediterranean soils incubated at relatively high temperature and low moisture content 33. These studies underline the importance of temperature and moisture content on the pesticide‐degrading ability of the soil microbiota, which accomplishes a key ecosystemic service responsible for natural pesticide attenuation.…”
Section: Discussionmentioning
confidence: 76%
“…It could explain why some authors concluded that the amount of bound residues seemed to be inversely proportional to mineralization. These results also explain why pesticide degradation is reduced (with increase in persistence) in areas characterized by elevated temperature and limited rainfall (Bouseba et al, 2009). Temperature.…”
Section: Effect Of Environmental Conditions (Water Content Temperature)mentioning
confidence: 60%
“…Alletto et al (2006) demonstrated that isoproturon mineralization was largely affected by temperature in both surface and subsurface soils but degradation seemed more sensitive to water content variations than temperature ones. Pesticide biodegradation could also be affected in temperate regions if global warming lead to drastic changes (Bouseba et al, 2009). For example, Levy et al (2007) showed that the harsh summer conditions of 2003 altered the structure of the microbial communities involved in isoproturon biodegradation and decreased severely isoproturon mineralization.…”
Section: Effect Of Environmental Conditions (Water Content Temperature)mentioning
confidence: 99%
See 1 more Smart Citation
“…Oxyfluorfen dissipation can be attributed to microbial degradation and depends on microbial species and temperature . Some authors have found that an increase in soil moisture level consistently decreased pesticide persistence and it has been related either to an increase in pesticide bioavailability or/and to an enhancement of soil microbial activity . Differences in degradation rates with soil moisture could be more related to changes in microbial population activity.…”
Section: Resultsmentioning
confidence: 99%